Предмет: Математика,
автор: Vane4ka1
Упроститите выражение
0,4*(0,9-57х)-0,9*(0,4-1 целая 37х)
Ответы
Автор ответа:
0
0,4 * (0,9 - 5/7х) - 0,9 * (0,4 - 1 3/7х) = 0,36 - 4/10*5/7х - 0,36 + 9/10*10/7х = - 2/7х + 9/7х = 7/7х = х
Автор ответа:
0
Вы умножали –4/10 на 5/7x и получили 2/7x. Внимательнее надо быть
Автор ответа:
0
Спасибо)))
Автор ответа:
0
= = = = =
Похожие вопросы
Предмет: Литература,
автор: sasha12345678912
Предмет: История,
автор: kyalbekovdaniel
Предмет: Математика,
автор: lavkajsksksnw
Предмет: Информатика,
автор: strawberry0011
Предмет: Алгебра,
автор: ErikCel